How to choose and interpret lung function tests in asthma and COPD - Matjaž Fležar; Stanislav Šuškovič; Škrgat Kristan; Mitja Košnik (Zdravniški Vestnik, 2011)
Background: Lung function testing consists of different tests to determine obstructive or restrictive lung disease. It includes tests for lung mechanics – measurements of lung volumes and flows, tests for gas exchange (diffusion capacity of the lung, blood gas analysis) and tests that confirm airway infllammation. In clinical setting a lot of those tests are ordered without considering their true diagnostic value, particularly on follow-up visits, where often the course of the disease is not predicted by other means. Results: The results of article present an overview of recommended lung function tests in follow-up and diagnostic procedure in asthma and COPD. Conclusion: Proper selection of lung function tests in following asthma and COPD patients rationalizes the management of those patients. The true value of repeating those lung function tests in decades of chronic lung disease is in answering the clinical questions regarding the patient’s status such as control of the disease and speed of lung function decline.